2020
DOI: 10.1002/hyp.13729
|View full text |Cite
|
Sign up to set email alerts
|

Moving beyond the catchment scale: Value and opportunities in large‐scale hydrology to understand our changing world

Abstract: Hydrological research is often focused at the catchment scale; but there are significant benefits of taking a broader spatial perspective (i.e., comparative hydrology) to advance the understanding of hydrological processes, especially in the context of global change. Indeed, many of the recently described "unsolved problems in hydrology" (Blöschl et al., 2019) refer to either global-scale processes (e.g., climate change), the hydrology of major physiographic zones (e.g., semi-arid or snowmelt regions) or requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 74 publications
1
13
0
Order By: Relevance
“…Reager et al [24] found a net sea level sink during 2002-2014 that could directly link with the increase in GWS or TWSA. This could further be supported by our study that as GWS increases, the sea level also increases in the East Coast; however, the subsurface catchment properties can act as a particularly strong filter on climate variability [66]. The effects of catchment size on climate-hydrology relationships, the degree of damping of climate signals related to hydrodynamic properties of the aquifer, as well as the influence of human stresses must be taken into consideration.…”
Section: Discussionsupporting
confidence: 58%
“…Reager et al [24] found a net sea level sink during 2002-2014 that could directly link with the increase in GWS or TWSA. This could further be supported by our study that as GWS increases, the sea level also increases in the East Coast; however, the subsurface catchment properties can act as a particularly strong filter on climate variability [66]. The effects of catchment size on climate-hydrology relationships, the degree of damping of climate signals related to hydrodynamic properties of the aquifer, as well as the influence of human stresses must be taken into consideration.…”
Section: Discussionsupporting
confidence: 58%
“…These high precipitation amounts mean that the Southern Alps act as “water towers” for the much drier areas to the east (Viviroli et al ., 2007), where water from the rivers originating in the Southern Alps is used intensively for electricity generation and irrigated agriculture. Just as this multi‐scale perspective is needed to understand terrestrial hydrology, precipitation delivery is also influenced by a number of interacting climate variables across different scales (Kingston et al ., 2020). For New Zealand, these include weather systems of tropical, temperate and sub‐polar origin, themselves affected by hemispheric‐scale atmospheric circulation patterns such as the Southern Annular Mode (SAM; Kidston et al ., 2009) and El Niño Southern Oscillation (ENSO; Gordon, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Closely inter-related key issues and challenges to large-scale hydrology were identified to improve prediction of hydrological systems behavior (surface/sub-surface) on large spatial and time scales (i.e. continental -multidecadal) under changing environmental conditions (Massei et al, 2018;Kingston et al, 2020). Large-scale hydrology depends on interactions across the ocean-atmosphere-vegetation/soil/aquifer system.…”
Section: Euro Friend-watermentioning
confidence: 99%